If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -20 = -2n Combine like terms: -6 + -20 = -26 -26 = -2n Solving -26 = -2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2n' to each side of the equation. -26 + 2n = -2n + 2n Combine like terms: -2n + 2n = 0 -26 + 2n = 0 Add '26' to each side of the equation. -26 + 26 + 2n = 0 + 26 Combine like terms: -26 + 26 = 0 0 + 2n = 0 + 26 2n = 0 + 26 Combine like terms: 0 + 26 = 26 2n = 26 Divide each side by '2'. n = 13 Simplifying n = 13
| 2x+10=110-10x | | 8x+9=2x-13 | | 4x=8x+6 | | x+4+5+2=3+2+2x | | 2*(x+3)-3(x+1)=x-13 | | b(b+2)+4b^2=5b^2+9b+8 | | 10x-13=3x-7 | | y=2x^3-7x^2-15x | | x+11=8+x | | x+11=8+c | | n-9=7 | | n+27=44 | | a-4=3a-6 | | 5y-10=2y-3x+11 | | (11x)=(5x+30) | | 2x+8=8x-1 | | 51-81.623= | | 0=(.25x^4)-(2x^2)-1 | | 7.2g+1.5=6+3.2g | | 2x^2+4x-10=0 | | 5x+2(x-3)=12x-5+14 | | 4(2x+3)-6x=18 | | -8x-(3x+6)=44-x | | 2t(t+5)+1=3t-3-t^2 | | 4x+4+2x= | | -3x+6=-3x+9 | | 10z+4=10(z+1)-6 | | 4i(6i)=48 | | (a-2)x=a^2-4 | | x^2-4bx+3b^2-4b-4=0 | | 2x+2x+46+x+14=180 | | -6a-15=-3a-21 |